Cardioprotective effect of rosmarinic acid against myocardial ischaemia/reperfusion injury via suppression of the NF-κB inflammatory signalling pathway and ROS production in mice - Wei Quan; Hui-xian Liu; Wei Zhang; Wei-juan Lou; Yang-ze Gong; Chong Yuan; Qing Shao; Na Wang; Chao Guo; Fei Liu (Taylor & Francis Group, 2021)
Context Rosmarinic acid (RosA), a natural poly-phenolic compound isolated from a variety of Labiatae herbs, has been reported to have a range of biological effects. Objective To investigate the cardioprotective effects of RosA against myocardial ischaemia/reperfusion (I/R) injury. Materials and methods Male C57BL/6J mice were given RosA (100 mg/kg) via intragastric administration. After 1 week of administration, the mice were subjected to 30 min/24 h myocardial I/R injury. The mice were randomly subdivided into 4 groups: Vehicle, RosA, Vehicle + I/R, and RosA + I/R. Infarct size (IS), cardiac function (including EF, FS), histopathology, serum enzyme activities, ROS changes, cis aconitase (ACO) activity, and specific mRNA and protein levels were assessed in vivo. HL-1 cells were pre-treated with or without RosA (50 μM), followed by stimulation with 9 h/6 h of oxygen and glucose deprivation/re-oxygenation (OGD/R). The cells were randomly subdivided into 4 groups: Vehicle, RosA, Vehicle + OGD/R, and RosA + OGD/R. Lactate dehydrogenase (LDH) levels, ACO activity, ROS changes and protein levels were measured in vitro. Results Treatment with RosA reduced the following indicators in vivo (p < 0.05): (1) IS (14.5%); (2) EF (-23.4%) and FS (-18.4%); (3) the myocardial injury enzymes CK-MB (20.8 ng/mL) and cTnI (7.7 ng/mL); (4) DHE-ROS: (94.1%); (5) ACO activity (-2.1 mU/mg protein); (6) ogdh mRNA level (122.9%); and (7) OGDH protein level (69.9%). Moreover, treatment with RosA attenuated the following indicators in vitro (p < 0.05): (1) LDH level (191 U/L); (2) DHE-ROS: (165.2%); (3) ACO activity (-3.2 mU/mg protein); (4) ogdh mRNA level (70.0%); and (5) OGDH (110.1%), p-IκB-a (56.8%), and p-NF-κB (57.7%) protein levels. Conclusions RosA has the potential to treat myocardial I/R injury with potential application in the clinic.